2015
DOI: 10.1007/s11420-015-9454-8
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Dose Mepivacaine Plus Fentanyl May Improve Spinal Anesthesia for Knee Arthroscopy

Abstract: Background: Previous work indicates that 30 mg isobaric mepivacaine 1.5% plus 10 μg fentanyl produces reliable anesthesia for knee arthroscopy with a more rapid recovery profile than 45 mg mepivacaine. Questions/Purposes: This randomized controlled trial compared plain mepivacaine to three reduced doses of mepivacaine with 10 μg fentanyl for spinal anesthesia. Methods: Following written informed consent, subjects undergoing outpatient knee arthroscopy were prospectively randomized into one of four groups: mepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Previously known as “transient neurologic toxicity” when initially described with lidocaine in 1993, it has also gone by the name of “transient radicular irritation” and presents with pain that can be light to severe with onset that occurs within 24 hours of injection [15] . TNS is used to currently describe such pain, lasting no more than a few days, originating in the gluteal region radiating to both lower extremities after a single injection of any spinal anesthetic [16] , [17] . Mepivacaine is an intermediate-acting local anesthetic with a reported duration of action of 90-150 minutes, which may offer a favorable pharmacokinetic profile for ambulatory arthroplasty without the historic TNS drawback.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously known as “transient neurologic toxicity” when initially described with lidocaine in 1993, it has also gone by the name of “transient radicular irritation” and presents with pain that can be light to severe with onset that occurs within 24 hours of injection [15] . TNS is used to currently describe such pain, lasting no more than a few days, originating in the gluteal region radiating to both lower extremities after a single injection of any spinal anesthetic [16] , [17] . Mepivacaine is an intermediate-acting local anesthetic with a reported duration of action of 90-150 minutes, which may offer a favorable pharmacokinetic profile for ambulatory arthroplasty without the historic TNS drawback.…”
Section: Introductionmentioning
confidence: 99%
“…Mepivacaine is an intermediate-acting local anesthetic with a reported duration of action of 90-150 minutes, which may offer a favorable pharmacokinetic profile for ambulatory arthroplasty without the historic TNS drawback. Several modern studies regarding other procedures have shown that mepivacaine has a faster recovery from induction, decreased urinary retention, and increased patient and surgeon satisfaction [16] , [17] , [18] , [19] , [20] . Until recently, mepivacaine had only been described for knee arthroscopy and anterior cruciate ligament reconstruction [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the lower dose of intrathecal doxylamine than subcutaneous doxylamine to achieve the local anaesthetic effects. Additionally, mepivacaine (1.41%; 7.76 μmol/kg) produced completely spinal motor and sensory blockades, while the dose is in accordance with clinical dosage of spinal anaesthesia with mepivacaine (30 mg, 1.5%) …”
Section: Discussionmentioning
confidence: 60%
“…Additionally, mepivacaine (1.41%; 7.76 lmol/kg) produced completely spinal motor and sensory blockades, while the dose is in accordance with clinical dosage of spinal anaesthesia with mepivacaine (30 mg, 1.5%). [36,37] Local anaesthetics inhibit nerve conduction through blocking voltage-gated Na + channels in the nerves. [38] Although pharmacological actions of doxylamine or triprolidine (i.e.…”
Section: Discussionmentioning
confidence: 99%